2013
DOI: 10.2215/cjn.06590712
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Physical Function and Physical Activity in Patients with CKD

Abstract: SummaryPatients with CKD are characterized by low levels of physical functioning, which, along with low physical activity, predict poor outcomes in those treated with dialysis. The hallmark of clinical care in geriatric practice and geriatric research is the orientation to and assessment of physical function and functional limitations. Although there is increasing interest in physical function and physical activity in patients with CKD, the nephrology field has not focused on this aspect of care. This paper pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
121
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 168 publications
(127 citation statements)
references
References 88 publications
1
121
0
5
Order By: Relevance
“…Evaluation of physical functioning in maintenance hemodialysis (HD) patients is recommended by the Kidney Disease Outcomes Quality Initiative clinical practice guidelines [1] and European Renal Best Practice guidelines [2], as decreased physical functioning leads to a reduced quality of daily life and higher risk of mortality in this patient population [1][2][3][4]. These guidelines recommend assessment of physical functioning using both self-reported and openfield measures of physical performance [2,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of physical functioning in maintenance hemodialysis (HD) patients is recommended by the Kidney Disease Outcomes Quality Initiative clinical practice guidelines [1] and European Renal Best Practice guidelines [2], as decreased physical functioning leads to a reduced quality of daily life and higher risk of mortality in this patient population [1][2][3][4]. These guidelines recommend assessment of physical functioning using both self-reported and openfield measures of physical performance [2,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in patients with CKD and patients on maintenance hemodialysis (MHD) have shown associations of physical activity with improved outcomes (10)(11)(12)(13)(14)(15)(16)(17)(18). However, it is uncertain whether the benefits of types and levels of physical activity apply for different outcomes, such as health-related quality of life (HRQOL), depression, and survival, in patients on MHD with diverse clinical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the device used in NHANES recorded uniaxial movement; hence, information on use of stationary bikes, elliptical trainers, or equipment that primarily involved upper body movement, such as rowing, may not have been recorded accurately. These might have resulted in underestimation of MVPA (29). However, these issues are unlikely to have led to underestimation of light-intensity activity.…”
mentioning
confidence: 99%